Impact of Pre-pregnancy Body Mass Index and The Incidence of Preeclampsia: Systematic Literature Review - Astrid Kizy Primadani; Elli Hidayati; Asry Novianty; Hirfaturrahmi Hirfaturrahmi (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
The incidence of preeclampsia is a leading cause of maternal morbidity and mortality worldwide, where the pre-pregnancy body mass index (BMI) is suspected to be one of the significant risk factors but requires a comprehensive synthesis of evidence. This study aims to analyze and synthesize scientific evidence regarding the influence of pre-pregnancy BMI on the incidence of preeclampsia. The method used is a systematic literature review with article searches in the Google Scholar, PubMed, Proquest, and ScienceDirect databases published in the last 5 years. The review results show that out of the 11 analyzed articles, all studies reported a significant relationship between increased pre-pregnancy BMI and the incident risk of preeclampsia. Woman who are underweight before pregnancy have a lower risk of preeclampsia, while those who are overweight or obese have higher incidence of preeclampsia. Regardless of adjustments for confounding factors, this study present that a high pre-pregnancy BMI is an risk factor for the occurrence of preeclampsia, making weight management before pregnancy very important as an effective primary prevention strategy.